2019
DOI: 10.1371/journal.ppat.1007945
|View full text |Cite|
|
Sign up to set email alerts
|

Cryptococcus neoformans resists to drastic conditions by switching to viable but non-culturable cell phenotype

Abstract: Metabolically quiescent pathogens can persist in a viable non-replicating state for months or even years. For certain infectious diseases, such as tuberculosis, cryptococcosis, histoplasmosis, latent infection is a corollary of this dormant state, which has the risk for reactivation and clinical disease. During murine cryptococcosis and macrophage uptake, stress and host immunity induce Cryptococcus neoformans heterogeneity with the generation of a sub-population of yeasts that manifests… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
64
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(72 citation statements)
references
References 118 publications
8
64
0
Order By: Relevance
“…Then, proteins were digested for 5 h at 30 °C with 500 ng rLys-C Mass Spec Grade (PROMEGA, Madison, WI, USA). Samples were then treated as previously described 71 as well as tryptic peptides analysis 71 with minor changes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, proteins were digested for 5 h at 30 °C with 500 ng rLys-C Mass Spec Grade (PROMEGA, Madison, WI, USA). Samples were then treated as previously described 71 as well as tryptic peptides analysis 71 with minor changes.…”
Section: Methodsmentioning
confidence: 99%
“…All data were searched using Andromeda 72 with MaxQuant software 73 , 74 version 1.5.3.8 against Homo sapiens reference proteome from Uniprot (20,399 entries) concatenated with GST-PTPN3-PDZ protein sequence, usual known mass spectrometry contaminants and reversed sequences of all entries as previously described 71 . The “match between runs” feature was applied between replicates with a maximal retention time window of 0.7 min.…”
Section: Methodsmentioning
confidence: 99%
“…Overtime, these yeast cells showed a decreased culturability on YPD agar plates, ending with about 1% of the cells still able to grow on agar at Day 8 of incubation. The phenotype observed in the in vivo subpopulation was resumed with delayed growth (increased latency) and low stress response (95). In total, the population obtained was homogenously composed of cells characterized as Viable but non-Culturable cells (VBNC) (Figure 1), phenotype well-known in many bacteria and first described in 1982 in Escherichia coli (105).…”
Section: Dormancy In C Neoformans Studied In Vitromentioning
confidence: 89%
“…Therefore, the authors worked on an in vitro model to be able to generate a high number of dormant yeast cells. Recently, the authors released and studied the standardized conditions allowing the generation of yeast cells harboring a phenotype close to that dormant cells generated in the lungs of infected mice (95). These conditions are based on a combination of conditions (low oxygen and limited nutrients) inspired from the Wayne and the Loebel models (two well-documented conditions enabling the generation of quiescent M. tuberculosis) (104).…”
Section: Dormancy In C Neoformans Studied In Vitromentioning
confidence: 99%
“…Some studies have also evidenced this phenomenon in wine yeasts [ 24 , 72 ] and explored the different stress conditions that could lead to the VBNC state in non- Saccharomyces yeasts. Thermosonication in B. bruxellensis [ 73 ] and hypoxic growth conditions in Cryptococcus neoformans [ 74 ] have triggered this state. Moreover, Wang et al [ 24 ] showed that cell-free S. cerevisiae supernatant produced the loss of culturability of Hanseniaspora uvarum , M. pulcherrima and T. delbrueckii , suggesting that the presence of some antimicrobial metabolites could induce the VBNC state.…”
Section: Discussionmentioning
confidence: 99%